Type 2 Diabetes, PUFAs, and Vitamin D: Their Relation to Inflammation - Ana L. Guadarrama-López; Roxana Valdés-Ramos; Beatríz E. Martínez-Carrillo (Journal of Immunology Research)
Chronic diseases have become one of the most important public health problems, due to their high costs for treatment and prevention. Until now, researchers have considered that the etiology of Type 2 diabetes mellitus (T2DM) is multifactorial. Recently, the study of the innate immune system has offered an explanation model of the pathogenesis of T2DM. On the other hand, there is evidence about the beneficial effect of polyunsaturated fatty acids (PUFA) n-3 and n-6 in patients with chronic inflammatory diseases including diabetes. Furthermore, high vitamin D plasmatic concentrations have been associated with the best performance of pancreatic β cells and the improving of this disease. In conclusion, certain fatty acids in the adequate proportion as well as 25-hydroxivitamin D can modulate the inflammatory response in diabetic people, modifying the evolution of this disease.